MURAT HÖYÜK EARLY BRONZE AGE METAL FIGURINE - ÖZdemir, Abdulkadir; Bamyaci, Abdulvahap Onur (Mersin University, 2022)
This study presents a detailed examination of a metal figurine found during the 2019 excavations at Murat Höyük, located on the bank of the Murat River in the Solhan district of the Province Bing¨ol in Eastern Anatolia. Because the mound was to be inundated by the Aşa?l Kaleköy hydroelectric dam, extensive salvage excavations were conducted at the site in 2019 under the directorship of the Elazl? Museum. Four main settlement phases (Medieval, Middle Iron, Early Iron, Early Bronze) were documented at the site with the earliest habitation dating to the Early Bronze Age III (2500-2200 BC). While figurines shaped out of clay, stone, and marble are more common in the archaeological record of Early Bronze Age (EBA) Anatolia, and metal figurines are relatively rare, a metal figurine (,statuette') was discovered in the EBA settlement level of Murat Höyük. In tenos of typological and stylistic details, the metal figurine of Murat Höyük appears unique in the 3rd millennium records of Mesopotamia, the Aegean, and the Balkans. The figurine depicts a standing nude with stylized hands and feet. Eye-sockets are marked as shallow pits, while the mouth is not indicated. Anos are stretched out on both sides; head is slightly inclined to the left; breasts are fashioned as applique protrusions; and pubic triangle is indicated with incised lines. The fact that stone mold and crucible fragments were found in the same level of the site suggests that the object was most probably produced locally by casting. Casting defects (flash lines) are observable on the surface. In this study, based on a comparative iconographic examination, we propose that a goddess is depicted here. With its unique characteristics, the Murat Höyük goddess figurine is a significant contribution to the repertoire of metal 'figurines' in Anatolia, Syria, and Mesopotamia with broader implications about EBA metallurgy, art, and belief systems. © 2022 Mersin University. All rights reserved.
Murat Höyük Erken Tunç Ça?i Metal Heykelci?i
Keywords: Bingöl; Early Bronze Age; Eastern Anatolia; Figurine; Goddess; Metalworking